Fracas five identified : picture show non-UPM students involved in brawl - The Star, (2011)
KUALA LUMPUR: Police have identified five students involved in Wednesday's fracas at the Universiti Putra Malaysia (UPM) Campus in Serdang, which resulted in fist fights and a shattered glass door.